2016
DOI: 10.1590/0104-6632.20160334s20150488
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Correlation of the Mass Transfer Coefficient for a Liquid-Liquid System With High Density Difference

Abstract: -To investigate the mass transfer behavior of a liquid-liquid system with high density difference (∆ρ≈500 kg/m 3 ), single drop experiments were performed by using the ternary chloroform-ethanol-water system. The mass transfer direction was from the dispersed phase to the continuous phase, while the aqueous phase was dispersed in chloroform to generate drops. The influences of drop diameter, initial solute concentration and temperature on the mass transfer were investigated. The effects of the drop diameter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The temperature of extraction is observed to increase the extraction yields as displayed in the 6 results from table 3 (Kemppainen et al, 2014;Vázquez et al, 2001). This enhancement is due to 7 the increase of the mass transfer coefficient at higher temperatures (Huang et al, 2016). Moreover 8 the increment of the temperature results in the improvement of the solute solubility and diffusion 9 coefficient and also decreases of solvent viscosity, which promotes the extraction (Al-Farsi and 10 Lee, 2008).…”
mentioning
confidence: 96%
“…The temperature of extraction is observed to increase the extraction yields as displayed in the 6 results from table 3 (Kemppainen et al, 2014;Vázquez et al, 2001). This enhancement is due to 7 the increase of the mass transfer coefficient at higher temperatures (Huang et al, 2016). Moreover 8 the increment of the temperature results in the improvement of the solute solubility and diffusion 9 coefficient and also decreases of solvent viscosity, which promotes the extraction (Al-Farsi and 10 Lee, 2008).…”
mentioning
confidence: 96%
“…The increase in overall coefficients is linked to molecular agitation and the drop-in viscosity of the medium, increasing the diffusion of the transferred chemical species at the interface. , …”
Section: Resultsmentioning
confidence: 99%
“…25 The increase in overall coefficients is linked to molecular agitation and the drop-in viscosity of the medium, increasing the diffusion of the transferred chemical species at the interface. 25,26 Concentration of the Surfactant. The experimental results obtained as a function of the concentrations of polysorbate 80 and Triton X-100 are used.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, West et al [48] found that the results were different as much as fivefold from Sherwood's, which was likely caused by the difference in purity of the benzene used in experiment. More recently, Huang et al [61] presented mass transfer study along single drop rising in a system with high density difference, and specific cleaning procedure was performed before each experiment run. Different influencing factors were involved.…”
Section: ◼ Drop Rising or Fallingmentioning
confidence: 99%